Preparation and Optimization of Electrospun Nylon‐6 Fiber‐Reinforced High Strength and Toughness Thermoplastic Polyurethane Composites for Potential Use in Prosthetic Heart Valves - Gaigai Duan; Xiuling Yang; Minmin Ding; Qijun Wu; Chunmei Zhang; Shaohua Jiang (Macromolecular Materials and Engineering)
Abstract The interfacial aspects of fiber composites are widely favored. Here, three composite strategies based on hot‐pressing, electrospinning, and impregnation of PA6 fibers are presented for the preparation of PA6 fiber‐reinforced thermoplastic polyurethane (PA6/TPU) composites. The morphologies of the electrospun fiber/matrix interface and the mechanical properties of the PA6/TPU composite are investigated. Under the optimal conditions, the tensile strength, Young's modulus, and toughness of the H‐PA6/TPU composite are respectively 29.45 ± 1.477 MPa, 47.28 ± 2.61 MPa, and 38.03 ± 1.996 MJ m−3. The tensile strength, Young's modulus, and toughness of the E‐PA6/TPU composite are 28.03 ± 1.411 MPa, 73.81 ± 4.16 MPa, and 24.12 ± 1.265 MJ m−3, respectively. The tensile strength, Young's modulus, and toughness of the I‐PA6/TPU composite are respectively 29.45 ± 1.477 MPa, 47.28 ± 2.61 MPa, and 38.03 ± 1.996 MJ m−3, and the elongation at break is ≈240%. Moreover, without loss of TPU properties, the impregnation method effectively improves the interface adhesion between the fiber and the matrix, and the mechanical properties of PA6/TPU composite are significantly improved even if the fiber content is low. The impregnation method is simple to operate and can be extended to other thermoplastic polymers and other fiber‐reinforced composites.